The Impact of China-Pakistan Economic Corridor on the Relations between India and Pakistan: Examining the implications of the China-Pakistan Economic Corridor on India-Pakistan relations (Journal of Advances and Scholarly Researches in Allied Education, 2022)
China has made a large foreign investment in the China-Pakistan Economic Corridor alsoknown as the China-Pakistan Economic Corridor, as part of its One Belt, One Road plan. The alliancebetween China and Pakistan will strengthen as a consequence of a 46 billion investment in cooperativeprojects slated to be completed over the next few years. Pakistan, on the other hand, will have a greaterinfluence on China's standing in the international community. The China-Pakistan Economic Corridor(CPEC) also has an impact on India-Pakistan ties. It is a territory whose sovereignty has been disputedby India and Pakistan since 1947, and Jammu and Kashmir is vital to the transportation route betweenPakistan and China. As a result, from a strategic standpoint, Jammu and Kashmir are critical. This seemsto point to a less-than-ideal situation in which CPEC stresses an already strained relationship betweenIndia and Pakistan. This is not a desirable circumstance. On the other side, one might imagine a moreoptimistic future in which the conflict in Kashmir is finally over.